Optimisation of isolation, characterisation and exploitation of oxidative enzymes for terpene and terpenoid biosynthesis in industry - Richardson, Sasha (My University, 2022)
Soybean (Glycine max) lipoxygenase (LOX) isozymes can convert terpenes into industrially favourable terpenoids through oxidation. In this study, the temperature and pH optima at which LOX-1 and LOX-2 functioned were investigated along with the shelf-life and recyclability of the enzymes. It was confirmed that both isozymes can be recycled as cross-linked enzyme aggregates (CLEAs) which can save time and costs in industrial settings. LOX-1 as compared to LOX-2 has a shelf-life of greater than 75 days whereas after 45 days in aqueous form at 4℃ LOX-2 had lost catalytic ability. LOX-1 was seen to work favourably after 16 weeks in lyophilised form, but LOX-2 had lost all activity. Through the assays used to determine the two enzymes’ activity LOX-1 shows optimal activity at pH 10 while LOX-2 worked best at pH 6.8. LOX-1 is stable for 24 hours over a range of pH values, pH 2 to 11 and at temperatures up to and including 55℃. LOX-2 was seen to be less robust with activity only being retained in buffers at a pH of 6 to 11 and in temperatures up to and including 45℃. LOX-1 displayed a Vmax value of 0.1137 µmol/s/mg protein, thus showing higher catalytic ability than LOX-2 with a Vmax value of 0.0183 µmol/s/mg protein. This is mirrored in the Km values whereby LOX-1 shows peak activity with 1.313 µmol sodium linoleate in 0.2 M boric acid (pH 10.0) at 25℃ while LOX-2 shows this activity when 2.335 µmol sodium linoleate in 0.2 M sodium phosphate buffer (pH 6.8) at 25℃ is present.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2022